Fostering Innovation in MSMEs through Internationalization: The Mediating Roles of Market Orientation and Entrepreneurship in West Java - Gunawan, Arien Arianti; Putri*, Mediany Kriseka; Toni, Alfita Syifa (JURISMA : Jurnal Riset Bisnis & Manajemen, 2023)
This study aims to investigate the effect of internationalization on innovation performance through the mediating factors of market orientation and entrepreneurship in SMEs in emerging markets. The research involved 175 export-ready SMEs in the West Java Province, utilizing a quantitative methodology. The analysis in this study employed Structural Equation Modeling-Partial Least Squares (SEM-PLS) and was processed using the SmartPLS software. Based on the findings of this research, it was determined that internationalization can influence innovation through the mediation of market orientation and entrepreneurship. Therefore, it is recommended for SMEs to recognize their unique value proposition by utilizing the value proposition design method. Additionally, SMEs are advised to maintain strategies that meet consumer needs. Keywords: MSMEs; Internationalization; Entrepreneurship Orientation; Marketing Orientation; Innovation